2020
DOI: 10.3390/ijms21155506
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Genome-Wide Association Study (GWAS) in Mastocytosis Reveal New Gene Polymorphisms Associated with WHO Subgroups

Abstract: Mastocytosis is rare disease in which genetic predisposition is not fully understood. The aim of this study was to analyze associations between mastocytosis and single nucleotide polymorphisms (SNPs) by a genome-wide association study (GWAS) approach. A total of 234 patients were enrolled in our study, including 141 with cutaneous mastocytosis (CM; 78 children and 63 adults) and 93 with systemic mastocytosis (SM, all adults). The control group consisted of 5606 healthy individuals. DNA samples from saliva or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Clinical signs of a bleeding diathesis, such as hematoma formation, bruising, prolonged bleeding after biopsies, gingival bleeding, epistaxis, gastrointestinal hemorrhage, conjunctival hemorrhage, menorrhagia or hemorrhagic ulcer disease occur in about 50% of patients with MC disease ( [7,19]; further references therein) and can contribute to deterioration in quality of life. Thus, bleeding diathesis represents a frequent and clinically relevant problem in MC disease, although severe or fatal bleeding seems to be rare [20][21][22][23].…”
Section: Mast Cells As Parts Of Bleeding Diathesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical signs of a bleeding diathesis, such as hematoma formation, bruising, prolonged bleeding after biopsies, gingival bleeding, epistaxis, gastrointestinal hemorrhage, conjunctival hemorrhage, menorrhagia or hemorrhagic ulcer disease occur in about 50% of patients with MC disease ( [7,19]; further references therein) and can contribute to deterioration in quality of life. Thus, bleeding diathesis represents a frequent and clinically relevant problem in MC disease, although severe or fatal bleeding seems to be rare [20][21][22][23].…”
Section: Mast Cells As Parts Of Bleeding Diathesesmentioning
confidence: 99%
“…The prevalence of MCAS, at least in Germany, is about 17% [4] and about 20% in the U.S. [5], and that of HAT was found to be 4-6% of the general population [6], hence both being common disorders. Two genome-wide association studies (GWAS; [7,8]) on patients with SM revealed different non-overlapping results with regard to the multiple mutations in a variety of genes. A recent GWAS on MCAS patients detected also a large number of SNPs without overlapping with the GWAS results in SM patients (Hänisch 2021, personal communication; manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, 14 SNPs have been associated with the development or phenotype of human mastocytosis in published studies. [17][18][19][20][21][22] Of these, 11 were directly genotyped or could be imputed from our stage 1 data (Table S7), but only one of these was significant: rs1800925 in the promoter region of IL13 at 5q31 (p imputed ¼ 0.008). This SNP has been linked to the development of adult SM and serum interleukin-13 levels 18 and inflammatory disorders such as chronic obstructive pulmonary disease.…”
Section: Associations With Other Genetic Factorsmentioning
confidence: 99%
“…15,16 Several constitutional genetic variants have been associated with the development of different mastocytosis phenotypes in relatively small candidate gene studies [17][18][19][20][21] and a recent single-stage genome-wide association study (GWAS) of 234 affected individuals. 22 Finally, it has been clearly established that constitutional genetic variation at several loci predispose to other myeloproliferative neoplasms (MPN). 23,24 To determine whether common genetic variation plays a role in predisposition to mastocytosis, we have performed a robust two-stage GWAS focusing on affected individuals that tested positive for KIT D816V regardless of clinical subtype to help ensure a genetically homogeneous cohort.…”
Section: Introductionmentioning
confidence: 99%
“…These consist of mutations associated with down-stream activation pathways (NRAS/KRAS), clonal epigenetic instability (TET2, DNMT3A, ASXL1) and survival (SRSF2, ASXL1, RUNX1). 45 These additional mutations should prompt the provider to rule out other associated neoplasms. Recent data have identified three mutations that are predictive of prognosis in patients with systemic disease and a more aggressive profile.…”
Section: Mastocytosis In Adultsmentioning
confidence: 99%